THE IMMUNOGLOBULIN (IgG) ANALYSIS OF IMPLANTATION MICE (Mus musculus L.) POST OVARIECTOMY AFTER TREATMENT OF BLACK SOYBEAN FLOUR EXTRACT (Glycine soja) - Yenny Febriana Ramadhan Abdi; Mahriani Mahriani; Kartika Senjarini; Rike Oktarianti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2021)
Black soybean is one type of plant that has estrogenic activity, it can act as a source of natural exogenous estrogen. Decreased estrogen hormone in the body due to ovariectomy and menopause, it affect on immune response (IgG). The purpose of this study was to determine the effect of black soybean extract on immune response (IgG) of implantation mice post ovariectomy. Twenty eight mice were grouped into 4 groups, group 1 (negative control), group 2 (positive control with the administration estradiol concentration 50 ppm), group 3 and 4 were treatment group with the administration of black soybean flour extract doses of 0.31 g/ml and 0.63 g/ml. The data were analyzed using One Way Anova and Duncan Multiple Range Test (DMRT) (p<0,05). The treatment with administration of black soybean flour extract for 10 days in implantation mice post ovariectomy showed that a dose of 0.31 g/ml and dose of 0.63 g/ml had an effect on increasing significantly the immune response (IgG), i.e 0,12987and 0,12996 respectively.